Administrative Specialist Staff in Saxony – Topical Challenges at the Example of the Meissen University of Applied Administrative Sciences - Nolden, Frank (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The measures suggested offer the Freestate of Saxony a chance to successfully shape and organise the demographic change in spite of a decrease of personnel and a loss of knowledge, by using optimised digital techniques based on a solid professional training.
Keywords: wyzwania demograficzne; sektor administracyjny; Wolny kraj związkowy Saksonia